ANALISI KESALAHAN BERBAHASA PADA TUGAS TEKS EKSPOSISI DAN TEKS IKLAN, SLOGAN, POSTER PESERTA DIDIK KELAS VIII SMP MUHAMMADIYAH BANTUL - Maulana Suwarno; Febiana Dwi Anggita; Nadila Taradiva (Jurnal Komposisi, 2020)
Indonesian is a language that is easy to learn, language is also the identity of a nation in the world. This study aims to describe the forms of language errors which include letters, punctuation and standard language errors at the junior high school level. To collect research data, the method used was the observation method with the basic technique of tapping and the advanced technique of the listening technique without engaging proficiently. The results of this study were subjected to the VIII grade students of SMP Muhammadiyah Bantul as the source of the analyzed data. The object of research is language errors in the spelling field in the exposition text material and ad text.